PTU-194 Does metabolic syndrome impact tumour pathology in oesophageal adenocarcinoma?. (28th May 2012) - Healy, L A; Howard, J; Reynolds, J V
Abstract : Introduction: Obesity is an established risk factor for both the increased incidence of oesophageal adenocarcinoma cancer (OAC), and adverse outcomes by increasing risk of recurrence and reducing survival in obese patients post oesophagectomy. The exact mechanism of this relationship is unclear but the pattern of fat distribution pattern is likely important. Abdominal obesity more closely reflects an increased visceral fat area and is associated with alterations in metabolic risk profile. The clustering of central obesity, hypertension, and raised plasma glucose, triglycerides and HDL cholesterol is also known as the metabolic syndrome (MetS). The processes underling the metabolic syndrome especially insulin resistance and increased leptin, can provide a favourable growth environment for malignant cells and may have a role in cancer progression. Methods: The aim of this prospective observational study of OAC patients was to examine the incidence of MetS and its relationship to tumour pathology in an Irish population. Patients underwent a metabolic and nutritional assessment prior to initiation of treatment. Visceral fat area was measured using CT scans. MetS was defined according to the International Diabetes Federation definition. 1 Results: 83 OAC patients (71 male: 12 female) were recruited with a median age of 64.6 years ± 1.0 (range 48–86). All patients underwent an oesophagectomy, with 42% (n=35) receiving neoadjuvant chemoradiotherapy. 58% of patients were either overweight or obese with a further 60% centrally obese. Males had significantly greater visceral fat area (p=0.031) despite no difference in total abdominal fat compared to females (p=0.757). The incidence of obesity may be underestimated as 41% of patients reported unintentional weight loss with 18% losing >5% of their usual body weight. MetS was diagnosed in 39% patients, which exceeds the population norms reported at 21%. 2 The presence of MetS was not associated with tumour length, depth of invasion, lymph node positive disease, clinical or overall pathological stage in males or females. Individual features of MetS were also not significantly related to the pathological staging of oesophageal cancer. Conclusion: We report an increased prevalence of MetS and central obesity in a cohort of Irish patients with OAC. Dysphagia and weight loss are common in the presentation of oesophageal cancer and may mask the effect of obesity and metabolic syndrome on the clinical pathological features of OAC in this cohort. Further research is needed to fully understand the underlying biological mechanisms linking obesity to oesophageal cancer. Competing interests: None declared. References: 1. Alberti KGMM, et al. Diabetic Medicine 2006;23 :469–80. 2. Waterhouse DF, et al. Ir J Med Sci 2009;178 :161–6.